New York Secondary Metals - Sampling and Evaluating Secondary Non-ferrous Metals (with Discussion) - T. A. Wright (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The sampling of waste materials containing copper, lead and tin has taken on a new significance within recent years, and is of increasing importance, on account of the entry of some of the copper refineries into this field and the tendency towards consolidations among the smelters. In the past, such material was sold on the basis either of a rough or grat) sample or of casual inspection of the lot. The two principal sources of this waste are the processes of fabrication and the scrapping of automobile, electrical, plumbing, railroad and other equipment. In both cases rnuch material can bc sorted, salvaged and sold by classification and grade to be melted "as is" or with the addition of new or virgin metal. The increasing care in classifying exercised in the large manufacturing plants tends to incrcase the proportion of this usable scrap; on the contrary, the increasing use of more complex and special non-ferrous alloys tends to makc sorting and grading more difficnlt in turnings, borings, clippings, etc., and conseqllcntly is making sampling of more moment. In tin, lead, alumiinum, and zinc furnace by-products such as ashes, drosses, skimmings, etc., the trade practice of evaluation has not varied much. For instance, tin drosscs, battery lcad, and aluminunl skimmings are ordinarily sold on what is called "metallic button" or "metallic recovery" or "metallic yield." Coppcr and Icad wastcl, howcvcr, is being sold more and more on actual copper and lead contents bascd on sarrlple and chemical analysts. This paper will be dcvotctl chiefly to the sampling of niaterials suitablc only for refining and recovery of one or more of the metals present. The methods described are often bascd on thc fact that but one, metal, such as copper, is to be paid for. The loss of volatile constituents in melting does not appreciably affect thc final copper result, as the "after-melting" assay can be readily calculated to the "bcfore-nltltingl' basis, but if smelter efficiency continues to increase, so that in tiltie zinc, for instance, may be rccovrred on a paying basis, thc method of sampling dirty brass, for example, will have to bc changed also. As a matter of fact, we may cxpect that improved refining proresses will make possible the partial reeovrry of lcad and tin which are now lost